(untitled) (Indian Journal of Animal Production and Management, 2013)
A total of 133 calving records were utilized to study the seasonality and diurnal variation in calving in swamp buffaloes of Assam. The highest calving was reported in the month of September (25.56%) and lowest (1.50%) in the month of January. In the season wise distribution, the highest calving was recorded in the post monsoon season (60.90%) and the lowest (6.02%) during the winter season, while no calving was recorded during pre monsoon season. Majority of the animals delivered their calves during the late night and early morning. The average body weight of male and female calves was 28.05± 0.58 kg and 27.14± 0.58 kg respectively. The sex ratio (male: female) was recorded as 45: 55.